PENGARUH KEJELASAN SASARAN ANGGARAN, SISTEM PENGENDALIAN INTERNAL, SDM DAN MOTIVASI TERHADAP KINERJA APARATUR DESA DI KEC. SINGINGI HILIR KAB. KUANTAN SINGINGI - Sischa, Sonia; Kamaruddin, Kamaruddin (Sultan Syarif Kasim State Islamic University, Riau, 2019)
This study aims to examine: (1) the influence of budget clarity on the performance of village officials, (2) the influence of Internal Control on the performance of village officials, (3) the influence of Human Resources on the performance of village officials, (4) the influence of Motivation on the performance of village officials. The study was conducted at a village located in the district of Singingi Hilir, Kuantan Singingi. The Result showed that (1) budget clarity has significant influence on the performance of village officials, (2) Internal Control has significant influence on the performance of village officials, (3) Human Resources has significant influence on the performance of village officials, (4) Motivation has significant influence on the performance of village officials.